Dose-Adjusted Etoposide, Doxorubicin, and Cyclophosphamide With Vincristine and Prednisone Plus Rituximab Therapy in Children and Adolescents With Primary Mediastinal B-Cell Lymphoma: A Multicenter Phase II Trial. Issue 33 (20th November 2021) - Burke, G. A. Amos; Minard-Colin, Veronique; Aupérin, Anne; Alexander, Sarah; Pillon, Marta; Delgado, Rafael; Zsíros, József; Uyttebroeck, Anne; Dartigues, Peggy; Miles, Rodney R.; Kazanowska, Bernarda; Chiang, Alan K.; et al.
Abstract : PURPOSE: A dose-adjusted etoposide, doxorubicin, and cyclophosphamide with vincristine and prednisone plus rituximab (DA-EPOCH-R) regimen has been shown to deliver excellent survival for adults with primary mediastinal large B-cell lymphoma (PMLBL) without the use of radiotherapy. No international prospective evaluation of this regimen has previously been reported in children and adolescents. PATIENTS AND METHODS: We conducted an international single-arm phase II trial involving patients younger than age 18 years with PMLBL who were to receive six courses of DA-EPOCH-R. The primary end point was event-free survival (EFS). Overall survival and toxicity were also assessed. This trial was registered (ClinicalTrials.gov identifier: NCT01516567 ). RESULTS: Analyses were based on 46 patients. The median age was 15.4 years (interquartile range: 14-16 years). The median follow-up was 59.0 months (interquartile range: 52.6-69.2 months). Fourteen events were observed (eight relapses or progressions (including three parenchymal CNS relapses), four residual lymphoma, and two second malignancies). The 4-year EFS was 69.6% (95% CI, 55.2 to 80.9), which did not differ from the rate observed historically ( P = .59). Seven deaths occurred (six disease-related and one second malignancy). The overall survival was 84.8% (95% CI, 71.8 to 92.4). Twenty-two patients (48%) reached dose levels ≥ 4. Nonhematologic adverse events grade ≥ 3 or cardiac adverse events grade ≥ 2 occurred in 47 of 276 (17%) courses and 30 of 46 patients (65%). CONCLUSION: DA-EPOCH-R did not improve the EFS compared with a historical control in this first prospective multisite international study of children and adolescents with PMLBL. Further studies are required to determine the optimum therapy for children and adolescents with this lymphoma.